2020
DOI: 10.1139/cjpp-2019-0251
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene improves methotrexate-induced functional alterations of the Madin–Darby kidney cells in a concentration-dependent manner

Abstract: Lycopene is one of the most potent antioxidants among carotenoids due to its ability to quench singlet oxygen and react with free radicals to reduce DNA damage. Methotrexate is widely used in the treatment of several types of cancers and autoimmune diseases. One of the most common side effects of a high-dose of methotrexate is kidney injury. In this study, we evaluated effects of lycopene on the Madin–Darby canine kidney cells (MDCK) treated with methotrexate through the estimation of their mitochondrial and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…LYC is a non-provitamin A carotenoid [13] , with a high antioxidant activity deriving from conjugated double bonds [14] , thus distinguishing it as more efficient than the other carotenoids [15] . Previous studies have shown that this activity is high both in vitro [16] and in vivo [17] and especially efficient in quenching singlet oxygen [18] . Except for preventing the cells damage induced by free radicals, LYC is also responsible for the formation of stronger intercellular bonds and faster cellular metabolism [13] .…”
mentioning
confidence: 90%
“…LYC is a non-provitamin A carotenoid [13] , with a high antioxidant activity deriving from conjugated double bonds [14] , thus distinguishing it as more efficient than the other carotenoids [15] . Previous studies have shown that this activity is high both in vitro [16] and in vivo [17] and especially efficient in quenching singlet oxygen [18] . Except for preventing the cells damage induced by free radicals, LYC is also responsible for the formation of stronger intercellular bonds and faster cellular metabolism [13] .…”
mentioning
confidence: 90%
“…The principal carotenoid, lycopene (Lyc), is a fat-soluble red pigment in tomatoes, pink grapefruit, papaya, and watermelon (Stojiljković et al, 2020). Lyc has recently attracted special attention as the most potent antioxidant among carotenoids (Rao and Agarwal, 2000).…”
Section: Introductionmentioning
confidence: 99%